Use of a single preoperative dose of misoprostol is efficacious for patients who undergo abdominal myomectomy - Celik, H; Sapmaz, E (Elsevier Science Inc, 2003)
Objective: To investigate the effectiveness of a single preoperative dose of misoprostol in abdominal myomectomies. Design: Placebo-controlled randomized prospective study. Setting: Department of obstetrics and gynecology in a university hospital. Patient(s): Twenty-five women with symptomatic uterine leiomyomas. Intervention(s): Among patients undergoing abdominal myomectomies, an hour before the operation women in the study group (n = 13) were given a single dose of vaginal misoprostol (400 mug); those in the control group (n = 12) were given placebo. Main Outcome Measure(s): Intraoperative blood loss, duration of operation, duration of postoperative hospitalization, and the need for blood transfusion were compared between the control and study groups. Result(s): Blood loss, operation time, and need for postoperative blood transfusion were significantly reduced in the group given vaginal misoprostol. No difference was observed among patients in terms of the time of hospitalization. Conclusion(s): A single preoperative dose of vaginal misoprostol is a simple, reliable method for reducing intraoperative blood loss and need for postoperative blood transfusion after abdominal myomectomies. (C) 2003 by American Society for Reproductive Medicine.
Keywords: abdominal myomectomy; blood loss; misoprostol; operation time